(3GdGYJHGQ aj GdfGSN hGdefShNs - (3eMeO Hf ehSi Hf YKeGf GHf MGRe, CHh HcQ, Rjf GdOjf, GdeYQha HGdMGRej,J (B584 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG cJGH GPcQ ajg eG GfJgJ Edi eYQaJg ef fGSN MOjK QShd Gddg Udi Gddg Ydjg hSde hefShNg hgh Yde Ldjd s
(3BNQgG (B:s
(3jfJgi HHGH Gdfgi Yf Gf jbGd eG TGA Gddg hTjJ s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B117 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B64s
Keywords: (3GdMOjK h GdeUWdMs